A sauropodomorph (Dinosauria, Saurischia) specimen from the Upper Triassic of southern Brazil and the early increase in size in Sauropodomorpha. Issue 4 (4th July 2021) - Müller, Rodrigo T.; Garcia, Maurício S.
ABSTRACT: Whereas sauropod dinosaurs from the Jurassic and Cretaceous Periods were the largest land animals that ever lived, some of their early relatives evolved relatively large bodies during the Triassic Period. The evolutionary pathways followed by the earliest sauropodomorphs towards the acquisition of massive bodies are poorly understood. However, new finds from South America and Africa are reshaping our knowledge of this issue. Here, we describe a new early and relatively large sauropodomorph represented by a partial postcranial skeleton excavated from Carnian-aged beds (Upper Triassic) of southern Brazil. The new specimen is recovered as a sauropodomorph more closely related to bagualosaurians than saturnaliids or other early-diverging forms in two phylogenetic analyses. The new specimen is generically indeterminate but provides important evidence of an early increase in body size in Sauropodomorpha, being significantly larger than that of coeval or older forms (except Bagualosaurus agudoensis ). Furthermore, the specimen is about 3.2 times heavier than Buriolestes schultzi, the earliest-branching sauropodomorph. The slender hind limbs and typical cursorial proportions present in the earliest sauropodomorphs are mostly maintained in the new specimen despite its larger body size.